(untitled) (Baghdad Science Journal, 2016)
Type 1 diabetes mellitus (T1DM) is an autoimmune disease frequently associated with autoimmune thyroid disease (AITD). The study is conducted at the Specialized Center for Endocrinology and Diabetes-Baghdad at Al-karkh side, during December 2013 up to April 2014. In this study, we investigate the prevalence of anti-thyroid peroxidase (anti-TPO) antibody in(80) type1 diabetic patients with (AITD) and (30) healthy controls .Blood samples are taken for investigation of thyroid tests by using Vitek Immunodiagnstic Assay System (VIDAS).Enzeme Linked Immunosorbent Assay (ELISA) is used to detect anti-thyroid antibody(anti-TPO). The results show that age, gender and BMI (body mass index) are similar in both groups, p>0.05. Among 80 type1 diabetic patients 15(18.8%) are positive. There is a highly significant difference (p0.05) between T3 &T4 and frequency of positive and negative (anti-TPO).